Pelatihan Guru dalam Pemanfaatan E-Modul Aktivitas Fisik Berbasis ICT Untuk Mencegah Stress Anak - Rohmalina; Dwi Tresna Santana, Fifiet; Rizkita, Diantifani; Musfita, Regita (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
The objective of this community service activity is to enhance the competence of early childhood education (PAUD) teachers in utilizing ICT-based physical activity e-modules to create enjoyable learning experiences while preventing stress in young children. The implementation method consisted of five main stages: needs assessment, training material development, training execution, classroom implementation mentoring, and result evaluation through questionnaires and observation. The results indicated significant improvement in three key indicators: ICT comprehension (from 47% to 87%), teacher involvement in teaching physical activities (from 55% to 75%), and teaching confidence (from 60% to 90%). The novelty of this program lies in the integration of physical activity and digital technology through interactive e-modules as a preventive approach to managing stress in early childhood education environments. This initiative not only enhances teachers' pedagogical capacity on an individual level but also offers a best-practice model that can be replicated nationally. Through a contextual and technology-based approach, the training reinforces the role of teachers as agents of educational transformation in the digital era and supports the creation of a healthy, adaptive, and holistic learning environment for Indonesian children.